Brain atrophy in chronic alcoholic patients: a quantitative pathological study. Issue 3 (March 1985) - Harper, C; Kril, J
Abstract : There are essentially no objective neuropathological data on brain atrophy in chronic alcoholic patients despite numerous neuroradiological studies which show a high incidence of shrinkage or atrophy. Therefore measurements were made of the intracranial volume (ICV) and brain volume (BV) in a necropsy study of 25 chronic alcoholic patients and 44 controls. The pericerebral space (PICS) was calculated according to the formula (formula; see text) The PICS will increase in patients with brain atrophy since the ICV remains constant throughout life. The mean PICS value was 8.3% in controls, 11.3% in the alcoholic group, 14.7% in alcoholics with superimposed Wernicke's encephalopathy (thiamine deficiency) and 16.2% in those alcoholics with associated liver disease. Thus there was a statistically significant loss of brain tissue in chronic alcoholic patients which appeared to be more severe in those with associated nutritional vitamin deficiencies or alcoholic liver disease.